La città di Ivrea tra salvaguardia e recupero del patrimonio architettonico del XX secolo - Giovanni Conca (In Situ)
The aim of this article is to present the dynamics of the valorisation process of modern architecture within the Italian regulatory framework for cultural heritage, and also to point out the difficulties of its safeguard due to various factors. In a context where the architectural legacy of the 20th century is poorly appreciated, the recognition of Ivrea’s modern neighbourhoods constitutes a model for initiating a protection policy for more recent architecture in Italy. Industrial city linked to the history of Olivetti, Ivrea is a unique architectural ensemble, comprising residential, industrial and social buildings of exceptional quality. Its inscription as Unesco’s World Heritage in 2018 is the result of research work and initiatives which have transformed the Piedmontese city, from the 1990’s onwards, into an experimental testing ground for theory and practice unprecedented in the country, aiming at the renovation of its architectural heritage.The ambition is to turn Ivrea into a place of culture and to offer a new image for the city; nevertheless, it is necessary to refer to the circumstances of the territory that has been suffering, for many years, from the effects of a crisis and a decrease of the resources available for its economic recovery.